Welas Asih Diri Sebagai Mediator Hubungan Antara Dukungan Sosial dengan Flourishing - Suharsono, M.; Wismanto, Y. Bagus (Jurnal Psikologi Perseptual, 2023)
This research aims to test the effect of social support on flourishing both directly and with self-compassion as a mediator. Participants were 124 adults from a higher education institution that used the tagline joyful learning and joyful working, with incidental sampling and data taken using a scale whose concept was taken from the flourishing scale compiled by Diener and Hone, social support was measured using the Oslo social support scale, and Neff's self-compassion scale. The analysis was carried out using mediation analysis from the JASP 16.1 program. The results show that self-compassion does not mediate the relationship between social support and flourishing, and self-compassion and social support are independently very significantly related to flourishing. Penelitian ini bertujuan menguji pengaruh dukungan sosial terhadap flourishing baik secara langsung maupun dengan welas asih diri sebagai mediator. Partisipan adalah 124 orang dewasa dari sebuah institusi pendidikan tinggi yang menggunakan tagline joyful learning dan joyful working, dengan incidental sampling dan data diambil dengan skala yang konsepnya diambil dari skala flourishing yang disusun oleh Diener dan Hone, dukungan sosial diukur dengan Oslo social support scale, dan self compassion scale dari Neff. Analisis dilakukan dengan analisis mediasi dari program JASP 16.1. Hasil menunjukkan bahwa welas asih diri tidak memediasi hubungan Dukungan sosial dengan flourishing, serta welas asih diri dan dukungan sosial secara mandiri berhubungan secara sangat signifikan terhadap flourishing.